Concentration and market size: lower bound estimates for the Brazilian industry - Marcelo Resende (Center for Economic Studies and ifo Institute (CESifo), 2008)
The paper estimates the lower bound for market concentration taking as reference the framework advanced by Sutton (1991). Quantile regression methods were considered in the context of the Brazilian manufacturing industry in 2005 and separate estimates were obtained for exogenous and endogenous sunk cost industries. The evidence favoured a convergence of the concentration lower bound towards zero in exogenous sunk costs industries in line with previous empirical evidence for developed countries. In ontrast, the magnitude was similar in the case of endogenous sunk cost industries what might reflect the low technological effort in that emerging economy.
Keywords: L11; 330; Concentration; market size; Wirtschaftskonzentration; Verarbeitendes Gewerbe; Sunk Costs; Marktstruktur; Brasilien